EFEKTIVITAS KEBIJAKAN PELAKSANAAN KERUKUNAN UMAT BERAGAMA - Sidik Ibrahim (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2016)
Harmony is the common goal of both government and religious adherents in Palu which is plural in terms of ethnic group and religion. As it is commonly known that plurality is not only a symbol of strength in society but also a source of conflict. Based on this, this paper is to examine the effectiveness of policy on religious harmony in Palu by portraying the condition of religious harmony in society and analyzing the role of the Inter-Religious Harmony Forum (FKUB) in Palu. It is concluded that, first, harmony in Palu is achieved due to piety of religious adherents. Second, the role of the Inter-Religious Harmony Forum (FKUB) in Palu is still weak. This is caused by the fact that the program is not yet rightly implemented due to the lack of financial support and the organizers do not know exactly their role and task. Third, the Inter-Religious Harmony Forum (FKUB) in Palu do not properly perform its task in driving religious harmony in society.